Expert stakeholder perspectives on warm-up and activation in high-performance snowsport: exploring current practices, challenges, and opportunities - Beck, L.; Bekker, S.; Scherr, J.; Verhagen, E.; Bolling, C.; Spörri, J. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Injury rates in high-performance snowsports, such as alpine and freestyle skiing and snowboarding, are known to be high. 1 Across different sports, sport-specific neuromuscular warm-up programs have been shown to be effective in preventing injury. 2,3 The aim of this study was to explore current practices, challenges and opportunities related to warm-up and activation in snowsports.